Development of probiotic orodispersible tablets using mucoadhesive polymers for buccal mucoadhesion. (1st November 2020) - Hoffmann, Anja; Fischer, Joerg T.; Daniels, Rolf
Abstract: Objective: Probiotic bacteria, such as different lactobacilli strains, have successfully been used to treat gingivitis and periodontitis or caries. By formulating probiotics as orodispersible tablet (ODT), the benefits of this dosage form could be utilized. Without any further measures, the probiotic bacteria will be eliminated too fast from the intended site of action, the oral mucosa. The use of mucoadhesive granules, composed of mucoadhesive polymer and probiotics, is a promising strategy to prolong the contact time between lactobacilli and oral mucosa without delaying disintegration. Methods: Three common mucoadhesive polymers, anionic Carbopol 971P NF, nonionic Metolose 65SH50 and cationic chitosan were included into tablets either by direct compression (DC) or after granulation with the probiotics. Disintegration, mucoadhesion of the tablets, and storage stability of the probiotics were characterized. Results: By incorporating a sufficient amount of polymer superior probiotic mucoadhesion could be achieved. All formulations based on granulated probiotics and mucoadhesive polymer fulfilled the Food and Drug Administration (FDA) acceptance level for disintegration of orodispersible tablets. These formulations exhibited excellent storage stability under refrigerated conditions over 30 months. Interestingly, ODTs including Carbopol 971P NF still proved superior mucoadhesion after long-term storage, whereas the mucoadhesive effect of Metolose 65SH50 and chitosan declined markedly. Conclusions: The results of this study suggest that Carbopol 971P NF was the most appropriate polymer for a probiotic mucoadhesive ODT.